2013
DOI: 10.48550/arxiv.1311.5804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high-statistics study of the nucleon EM form factors, axial charge and quark momentum fraction

Abstract: We present updated results for the nucleon axial charge and electromagnetic (EM) form factors, which include a significant increase in statistics for all ensembles (up to 4000 measurements), as well as the addition of ensembles with pion masses down to m π ∼ 195 MeV. We also present results for the average quark momentum fraction. The new data allows us to perform a thorough study of the systematic effects encountered in the lattice extraction. We concentrate on systematic effects due to excited-state contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 13 publications
5
19
0
Order By: Relevance
“…None of the other observables show this kind of reversal in behavior between 254 MeV and lower pion masses. Excluding our two lightest m π ensembles, our results are consistent with a recent calculation [9,42] that uses O(a) improved Wilson fermions and the summation method for 195 MeV m π 649 MeV. In that calculation, chiral extrapolation to the physical mass is statistically consistent with experiment and g A (∆t) typically increases 10% when ∆t increases by 0.5 fm, which is the behavior for our 254 MeV ensemble.…”
Section: Lattice Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…None of the other observables show this kind of reversal in behavior between 254 MeV and lower pion masses. Excluding our two lightest m π ensembles, our results are consistent with a recent calculation [9,42] that uses O(a) improved Wilson fermions and the summation method for 195 MeV m π 649 MeV. In that calculation, chiral extrapolation to the physical mass is statistically consistent with experiment and g A (∆t) typically increases 10% when ∆t increases by 0.5 fm, which is the behavior for our 254 MeV ensemble.…”
Section: Lattice Resultssupporting
confidence: 88%
“…The presence of substantial excited-state contaminations in x u−d was first hinted at in Ref. [40] for m π = 493 MeV, later substantiated by an early report from the present study [15] and at m π = 373 MeV [41], and recently further confirmed at m π ≥ 195 MeV [42].…”
Section: Lattice Resultssupporting
confidence: 82%
“…In this paper, we study the efficiency of AMA when combined with the highly efficient locally deflated SAP-preconditioned GCR solver. In an extension of our previous studies [13,24,25], we apply AMA to the calculation of the axial charge of the nucleon from three-point functions with large source-sink separations of around 1.5 fm and above on large lattices satisfying m π L > 4 with N f = 2 flavours of dynamical quarks. In addition, we also determine the scalar and tensor charges of the nucleon on the same configurations.…”
Section: Introductionmentioning
confidence: 99%
“…We find that for the axial charge as extracted from ratios of correlation functions, large source-sink separations are required to reliably suppress excited-state contaminations, which become visible only at high enough statistics, and that values close to the experimental one are obtained from the largest source-sink separations studied. The summation method [9,13,25] is able to extract the asymptotic behaviour already from moderate source-sink separations, but still profits greatly from having precise measurements at large separations.…”
Section: Introductionmentioning
confidence: 99%
“…For pion masses at the physical point, however, nucleon correlation functions suffer from a well-known signal-to-noise problem [5], which is only exacerbated in the calculation of nucleon three-point functions. For many years, lattice computations of the axial charge have been subject to underestimation, with a variety of systematic sources investigated for this effect, such as: finite volume [6][7][8][9][10], excited-state contamination [11][12][13] and even thermal effects [14]. Not all collaborations, however, have obtained consistent results, for example, finite volume effects could not be substantiated [15], excited-state effects were not seen in the studies [16,17], and thermal effects could not be reproduced [18].…”
Section: Introductionmentioning
confidence: 99%